Optimal agronomic factors for commercial sweet potato production (Ipomoea batatas L., cv. Jonathan) on the Peruvian Central Coast - Julca-Izquierdo, Karen (2021)
The objective of the present study was to analyze the effect of three factors as type of seed, seed density and crop fertilization on the yields of commercial sweet potato roots cv. Jonathan. Four variables were analyzed: total root yield, commercial roots yield, non-commercial root yield and total dry matter. The experiment design was a randomized complete block factorial arrangement 2Sx2Dx2F, with two levels in each factor: common seed and basic seed, 20 cm and 40 cm spacing between cuttings, low and medium fertilization. The results showed that there is no interaction among the factors evaluated. The average planting density factor was statistically higher in all treatments with the spacing of 20 cm between cuttings; both commercial roots yield and other variables evaluated. In all treatments, commercial yield ensured the economic return of production, T5 treatment (basic seed, 20 cm spacing between cuttings and low fertilization) showed the highest yield average with 23.35 kg, and the average of the entire harvest of 83.84% of commercial roots.